2007
DOI: 10.1016/j.fgb.2006.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of conidial dispersal in the toxic mold Stachybotrys chartarum

Abstract: Conidial dispersal in Stachybotrys chartarum in response to low-velocity airflow was studied using a microflow apparatus. The maximum rate of spore release occurred during the first 5 min of airflow, followed by a dramatic reduction in dispersal that left more than 99% of the conidia attached to their conidiophores. Micromanipulation of undisturbed colonies showed that micronewton μN) forces were needed to dislodge spore clusters from their supporting conidiophores. Calculations show that airspeeds that normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
1
13
1
Order By: Relevance
“…These findings support the results of others on the common occurrence of Aspergillus and Penicillium conidia in air samples (Shen et al, 2007;Spicer and Gangloff, 2008). It was also observed for some isolates that the airflow did not cause sufficient disturbance to dislodge and/or liberate a large proportion of the conidia (Tucker et al, 2007). Therefore, in support of the theory that splashing rain may dislodge and disperse microfungal spores (Ntahimpera et al, 1998;Travadon et al, 2007), washing the culture with PSS resulted in all cases in an immediate massive release of colony forming units from the cultures (Figure 4).…”
Section: Discussionsupporting
confidence: 91%
“…These findings support the results of others on the common occurrence of Aspergillus and Penicillium conidia in air samples (Shen et al, 2007;Spicer and Gangloff, 2008). It was also observed for some isolates that the airflow did not cause sufficient disturbance to dislodge and/or liberate a large proportion of the conidia (Tucker et al, 2007). Therefore, in support of the theory that splashing rain may dislodge and disperse microfungal spores (Ntahimpera et al, 1998;Travadon et al, 2007), washing the culture with PSS resulted in all cases in an immediate massive release of colony forming units from the cultures (Figure 4).…”
Section: Discussionsupporting
confidence: 91%
“…Our data for the spore release rates were found several times higher than the data reported by Tucker et al 2007), who investigated fungal spores release of A. niger from gypsum wallboards. This may be mainly because of the differences in air speeds.…”
Section: Initial Spore Density and Spore Release Rate For Different Scontrasting
confidence: 84%
“…As mentioned above, air speed has a direct positive correlation with spore release beyond a threshold speed. Tucker et al (2007) reported the air speed of 1.6 m s -1 , whereas the air speed of 5 m s -1 was used in the present study. The drag force exerted on the fungal spores under the blowing speed of 5 m s -1 was much greater than that under the blowing speed of 1.6 m s -1 .…”
Section: Initial Spore Density and Spore Release Rate For Different Smentioning
confidence: 99%
“…and Chaetomium spp.) growing on damp building materials do not readily become airborne and/or lose their culturability soon after liberation (21,29,45,47) and may therefore not be detected during air or dust sampling. Correct species identification of the fungi is also important, since new research has indicated that species-specific metabolites, like atranone C produced by…”
mentioning
confidence: 99%